Fast and Flexible Space Debris Risk Assessment for Satellites. Issue 3 (December 2016) - Gulde, Max; Kempf, Scott; Schäfer, Frank
ABSTRACT: The rapid increase in uncontrolled high velocity objects orbiting earth poses a continuously growing failure potential for ongoing and future space missions. Despite increasing efforts to mitigate collisional risks, e.g. via active debris removal, potential solutions are currently only emerging at the horizon, emphasizing the importance of space debris related risk assessment. However, traditional impact shielding requirements for manned mission cannot directly be transferred to unmanned missions. Instead of restricting the analysis to the outer hull, it is necessary to directly assess the failure risk on the level of individual, internal components. Here, we outline a newly developed deterministic methodology to enable the evaluation of system level effects on the spacecraft. In particular, we employ a computational model based on available probabilistic debris models and component-specific ballistic limit equations. The methodology has been implemented into the easily accessible software tool PIRAT (Particle Impact Risk and Vulnerability Assessment Tool).